Fauna and diversity of the manure-inhabiting Mesostigmata (Acari) in Kerman County, South Eastern Iran - Elham Arjomandi; Shahrooz Kazemi; Ali Afshari (Persian Journal of Acarology)
A faunistic survey was carried out on the manure-inhabiting mesostigmatic mites in Kerman County, South Eastern Iran, during 2011–2012. In this research, 36 species belonging to 23 genera and 14 families were collected and identified of which Ameroseius pavidus (C.L. Koch) (Ameroseiidae) and Trachytes baloghi Hirschmann & Zirngiebl-Nicol (Trachytidae) are considered here as new records for Iran mite fauna. The Shannon-Wiener’s diversity index was also calculated for these mite communities within cow, poultry, and sheep manures in nine different districts of the County. Mite community within cow manures, with 31 species, was more diverse than poultry and sheep manures which had 14 and 13 species, respectively. The highest (2.2±0.07) and the lowest (0) mean values of diversity index were calculated for Sekonj and Langar districts, respectively. Based on relative frequency, Uroobovella marginata (C.L. Koch), U. difoveolata Hirschmann & Zirngiebl-Nicol, and Androlaelaps casalis (Berlese) were the most dominant species in cow, sheep, and poultry manures, respectively. On the other hand, Macrocheles merdarius (Berlese) and Androlaelaps casalis (Berlese) were the most widespread species.